The role of Pregnancy-Specific Glycoprotein 1a (PSG1a) in regulating the innate and adaptive immune response - Martinez, Fernando Fabian (2013)
Among several explanations for the acceptance of the fetus, the one that suggests that the maternal immune system is suppressed or modified has been the subject of many studies. Thus, it has been proposed that the cells of innate immune system might be able to distinguish the pregnant from the non-pregnant state producing a signal, the so-called signal P. We have previously proposed that pregnancy-specific glycoprotein 1a (PSG1a), a representative member of the main glycoprotein family secreted by placental trophoblast, may modulate the activation of antigen-presenting cells promoting the T-cell shift of the maternal cell immunity toward a less harmful phenotype. In this review, we summarize current knowledge concerning the contribution of pregnancyspecific glycoprotein 1a (PSG1a) to modulate the maternal innate and adaptive immune response in order to assure a successful pregnancy.